Sand dune activity in north-eastern Patagonia - del Valle, Hector Francisco (2008)
The Valdes Peninsula has the most noticeable aeolian landforms of the Patagonian drylands. The southern sector of the peninsula is affected by the advance of several fronts of active sand dunes grouped in discrete megapatches. The objectives of the study were to: (1) analyse the morphology of sand dunes, and (2) measure the migration rates and orientation of the sand dunes along a 33-year period (1969-2002). These studies used a series of field techniques in conjunction with aerial photography and satellite data, such as AVIRIS and Landsat imagery. Four main types of active sand dune forms were identified: (1) compound linear; (2) compound transverse; (3) compound dome-shaped; and (4) complex dome-shaped. Because of the windy climate, dune mobility is high; there is an eastward migration to an average speed of 9.1±2.7 m yr-1. Despite this high rate and since observed changes in the total area of active dunes were small, active processes of vegetation encroachment are deducible. Thus, wind and effective rainfall appear as the main factors regulating the process, in short and long-term, respectively. Although the orientation and disposition of the dunefields is in agreement with the prevailing west winds, the active dunes present a variety of forms, which reflect local variations in the wind flow. The circulation is strongly influenced by the shape of the coastline and the actual existence of the dunefields is due to this friable windward coast found nowhere else in Patagonia.